Correlation Between Bacterial Count and Duration of Tracheostomy Tubes Use - Kusuma, Angga; Hariwiyanto, Bambang; Wulandari, Dian Paramita; Johan, Andrew (RSUP Dr. Kariadi, 2026)
BACKGROUND: Tracheostomy tubes (TTs) are life-sustaining medical devices widely used for patients with upper airway obstruction or requiring prolonged mechanical ventilation. However, TTs serve as an indwelling substrate that promotes bacterial colonization and biofilm formation, particularly by resistant pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus. Despite the well-recognized clinical risks, evidence correlating the duration of TT use with quantitative bacterial load in the Indonesian hospital setting remains limited, creating a gap in local clinical guidance for tube replacement scheduling. AIM: To analyze the correlation between TT duration of use and bacterial colony count (CFU/mL), and to identify the predominant colonizing pathogens in order to inform evidence-based infection prevention and tube replacement timing. METHOD: This cross-sectional observational study was conducted from July 2020 to January 2021 at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. A total of 20 polyvinyl chloride (PVC) Portex™ tracheostomy tubes were collected via consecutive sampling from patients undergoing decannulation procedures. Bacterial cultures were performed at the Department of Microbiology, Universitas Gadjah Mada, with bacterial load expressed as colony-forming units per milliliter (CFU/mL). Spearman’s rank correlation was used for statistical analysis. RESULTS: Mean bacterial counts (CFU × 10³/mL) were 48.5, 9,853.83, and 28,200.00 for TT use durations of <30 days, 30–90 days, and >90 days, respectively. Spearman’s rank correlation demonstrated a strong positive association between duration and bacterial count (r = 0.70, p = 0.01). Pseudomonas aeruginosa was the most prevalent organism, identified in 60% of tubes. CONCLUSION: Duration of TT use exceeding 30 days is significantly correlated with higher bacterial colonization burden. Pseudomonas aeruginosa was the predominant pathogen. These findings support the recommendation for scheduled TT replacement within 30 days as an infection control measure in tracheostomized patients.